2012
DOI: 10.1021/jo301225v
|View full text |Cite
|
Sign up to set email alerts
|

Gymnothelignans A–O: Conformation and Absolute Configuration Analyses of Lignans Bearing Tetrahydrofuran from Gymnotheca chinensis

Abstract: Fifteen new lignans, gymnothelignans A−O (1−15), bearing tetrahydrofuran with variable conformations belonging to three potentially related skeletons were isolated from Gymnotheca chinensis Decne. The structures were elucidated by means of detailed spectroscopic analysis. Absolute configurations were assigned using X-ray singlecrystal diffraction and chemical transformations. Moreover, by the homology, compounds 1−11 and eupomatilones were confirmed to have uniform R-configuration at C-5. However, a synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…The correlations of H-6 to CH 3 -17, and H-9 to CH 3 -18 suggested H-6/H 3 -17 and H-9/ H 3 -18 were cofacial. The vicinal coupling constants of H-6/H-7 (J = 2.0 Hz) and H-8/H-9 (J = 5.4 Hz) were in close agreement with those observed in gymnothelignan L (He et al, 2013). Detailed HMBC analysis suggested that the structure of 1 was very similar to Phytochemistry Letters 8 (2014) 38-40 those of gymnothelignan L except for the replacement of the methylenedioxy by two methoxy groups at C-12 and C-13.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The correlations of H-6 to CH 3 -17, and H-9 to CH 3 -18 suggested H-6/H 3 -17 and H-9/ H 3 -18 were cofacial. The vicinal coupling constants of H-6/H-7 (J = 2.0 Hz) and H-8/H-9 (J = 5.4 Hz) were in close agreement with those observed in gymnothelignan L (He et al, 2013). Detailed HMBC analysis suggested that the structure of 1 was very similar to Phytochemistry Letters 8 (2014) 38-40 those of gymnothelignan L except for the replacement of the methylenedioxy by two methoxy groups at C-12 and C-13.…”
Section: Resultssupporting
confidence: 85%
“…Compound 1 exhibited a greater cytotoxicity than gymnothelignan L against the HepG2 cell line, indicating that the compounds with methoxy groups at C-12 and C-13 possess greater cytotoxicity than the corresponding 6/9 epoxy dibenzocyclooctadiene lignans. All of the gymnothelignans isolated from G. chinensis possess an epoxy bridge (He et al, 2013). The results of the cell viability assay indicated that the epoxy bridge functional group plays an insignificant role in a compound's cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous phytochemical investigation on G. chinensis, we isolated 27 new lignans belonging to the dibenzocyclooctene, biphenyl tetrahydrofuran, eupodienone, and norlignan series [3][4][5][6][7][8], while our previous study on the constituents of G. involucrate led to the isolation of a flavonoid glycoside, two sterols, and two lignans [9,10]. In our continuing endeavor to discover unique and new structures from these plants, four rare polycyclic spiro lignans, gymnothespirolignans E, D, C, and F (1)(2)(3)(4), and four new biphenyl tetrahydrofuranone lignans were isolated from the whole plant of G. involucrata. Selected compounds were evaluated for their fungicidal and insecticidal activities.…”
mentioning
confidence: 99%
“…1), of which four were rare polycyclic spiro lignans (1)(2)(3)(4), and the other four were atropisomer biphenyl lignans (5)(6)(7)(8) 4.12, 3.84, 3.83 (each 3 H, s); δ C 59.9, 56.6, 56.2], one quaternary carbon (δ C 94.9), and two aromatic ring moieties [δ H 6.71 (1 H, s), 7.45 (1 H, s); δ C 150. 7, 149.6, 148.8, 145.3, 140.2, 139.2, 137.3, 132.8, 125.5, 110.4, 107.6, 99.8].…”
mentioning
confidence: 99%